Storage stability and antioxidant properties of chicken ball incorporated with threadfin bream (Nemipterus Japonicas) hydrolysate / Normah Ismail, Aishah Netylia Amat Ruba’iee and Kyaw Zay Ya - Ismail, Normah; Amat Ruba’iee, Aishah Netylia; Kyaw, Zay Ya (Universiti Teknologi MARA, Negeri Sembilan, 2019)
This study was carried out to determine the antioxidant activity of threadfin bream (Nemipterus Japonicas) hydrolysate (TFBH) in comparison with the commercial antioxidants; α-tocopherol and LYK Nanox 189 and to evaluate the oxidative stability of chicken balls added with 20% TFBH during the 15 days storage at 4 ᵒ C. TFBH was prepared by hydrolysis with Alcalase at pH 8.5, 60 ᵒ C, enzyme/substrate ratio of 2% for 2 hours. The results showed some antioxidant activities of the hydrolysate even though the activity was lower than the commercial antioxidants. This was based on the ferric reducing antioxidant power (FRAP) analysis and 2, 2-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity. Based on the induction time measured by Rancimat, TFBH when added into the chicken balls was capable of delaying the oxidation process during the 15 days storage at 4 ᵒ C. The observation was also supported by peroxide and TBARS values. Therefore, TFBH can be used in food to delay the oxidation process during storage.